Digital Transformation of Express Industry - Huang, Chen; Zuo, Xuelian; Chen, Tongtong (International Journal of Computer Science and Information Technology, 2024)
As a key component of the modern service industry, the express industry plays an increasingly important role in economic and social development. In recent years, due to the continuous evolution of the Internet, big data, artificial intelligence and other technologies, the express delivery industry has entered a period of opportunity and challenge of digital transformation. Digital transformation can not only improve the operational efficiency and service quality of the courier industry, but also bring consumers a more convenient and efficient courier service experience. This paper provides an in-depth analysis of the digital transformation of the courier industry, the background of the times, the system sorted out the many challenges it faces, and targeted coping strategies, in order to provide constructive reference for the sustainable development of the courier industry.